Vulnerability of drug‐resistant EML4‐ALK rearranged lung cancer to transcriptional inhibition. Issue 7 (17th June 2020) - Paliouras, Athanasios R; Buzzetti, Marta; Shi, Lei; Donaldson, Ian J; Magee, Peter; Sahoo, Sudhakar; Leong, Hui‐Sun; Fassan, Matteo; Carter, Matthew; Di Leva, Gianpiero; Krebs, Matthew G; Blackhall, Fiona; et al.
Abstract: A subset of lung adenocarcinomas is driven by the EML4‐ALK translocation. Even though ALK inhibitors in the clinic lead to excellent initial responses, acquired resistance to these inhibitors due to on‐target mutations or parallel pathway alterations is a major clinical challenge. Exploring these mechanisms of resistance, we found that EML4‐ALK cells parental or resistant to crizotinib, ceritinib or alectinib are remarkably sensitive to inhibition of CDK7/12 with THZ1 and CDK9 with alvocidib or dinaciclib. These compounds robustly induce apoptosis through transcriptional inhibition and downregulation of anti‐apoptotic genes. Importantly, alvocidib reduced tumour progression in xenograft mouse models. In summary, our study takes advantage of the transcriptional addiction hypothesis to propose a new treatment strategy for a subset of patients with acquired resistance to first‐, second‐ and third‐generation ALK inhibitors. Synopsis: Acquired drug resistance to ALK inhibitors prevents the effective management of lung cancer. This study shows that treatment with CDK inhibitors may be tested as an alternative upon development of resistance. EML4‐ALK‐mutant cells were sensitive to CDK inhibition, which resulted in apoptosis induction. CDK treatment reduced tumour growth in crizotinib‐ and alectinib‐resistant mouse models. Transcriptional perturbation was the main outcome of treatment with alvocidib or THZ1. Abstract : Acquired drug resistance to ALK inhibitors prevents the effective management of lung cancer. This study shows that treatment with CDK inhibitors may be tested as an alternative upon development of resistance.